Workplace industrial relations in the 1980's - Batstone, Eric (1988)
The discussion focused upon the period from Donovann to the late 1970s. However, many commentators have argued that the 1980s have seen a transformation in the nature of workplace industrial relations. This article seeks to assess, from the available evidence, how far this is indeed the case.
Photocopy.
Source: The Reform of Workplace Industrial Relations, Myth and Evidence. Chapter 5. Oxford: Clarendon Press, 1988. pp. 179-217.
Keywords: Working class -- Great Britain; Industrial organization -- Great Britain; Industrial relations. -- Great Britain